C-arm Lipiodol CT in transcatheter arterial chemoembolization for small hepatocellular carcinoma - Li, Jian-Jun; Zheng, Jia-Sheng; Cui, Shi-Chang; Cui, Xiong-Wei; Hu, Cai-Xia; Fang, Da; Ye, Lin-Chao (World journal of gastroenterology : WJG, 2015)
To investigate the value of C-arm Lipiodol computed tomography (CT) for intra-procedural hepatocellular carcinoma (HCC) lesion detection during transcatheter arterial chemoembolization (TACE). Forty patients (37 male, 3 female; mean age, 52.6 ± 12.5 years, age range: 25-82 years) diagnosed with HCC were enrolled in this study. All patients underwent 64-slice CT 1-2 wk before TACE. During the procedure, hepatic angiography was performed first. Following diagnostic embolization with Lipiodol injected into the hepatic artery, a C-arm CT scan was immediately conducted (C-arm Lipiodol CT). If new HCC lesions were confirmed, gelfoam particles were super-selectively injected into the tumor-nourishing blood vessel. A Lipiodol CT scan was performed 7-14 d after TACE. All images acquired from 64-slice CT, digital subtraction angiography (DSA), C-arm Lipiodol CT and Lipiodol CT were retrospectively reviewed by four radiologists and the number of detected lesions in each examination was counted, respectively. The results of Lipiodol CT were taken as the diagnostic reference. Alpha-fetoprotein values were examined both before and after TACE. This study only takes into account the lesions that were not found or were considered suspicious on 64-slice CT before TACE. Preprocedural 64-slice CT detected a total of 13 suspicious lesions in the 40 patients. DSA detected ten definite and four suspicious lesions. C-arm Lipiodol CT detected 71 lesions in total and Lipiodol CT confirmed 67 lesions with a diameter range of 3-12 mm. Four false-positive lesions, which were detected by C-arm Lipiodol CT, were considered to be hepatic artery-portal vein fistulas. The average alpha-fetoprotein values before and after TACE were significantly different (452.3 ± 192.6 ng/mL vs 223.8 ± 93.2 ng/mL; P = 0.039). C-arm Lipiodol CT has a higher diagnostic sensitivity for small HCC lesions. This technique may help physicians make intraprocedural decisions to provide patients with earlier treatment.